2016
DOI: 10.1002/jbmr.2996
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Sclerostin Alleviates Radiation-Induced Bone Loss by Protecting Bone-Forming Cells and Their Progenitors Through Distinct Mechanisms

Abstract: Focal radiotherapy is frequently associated with skeletal damage within the radiation field. Our previous in vitro study showed that activation of Wnt/β-catenin pathway can overcome radiation-induced DNA damage and apoptosis of osteoblastic cells. Neutralization of circulating sclerostin with a monoclonal antibody (Scl-Ab) is an innovative approach for treating osteoporosis by enhancing Wnt/β-catenin signaling in bone. Together with the fact that focal radiation increases sclerostin amount in bone, we sought t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 54 publications
9
117
1
Order By: Relevance
“…The focal irradiator used in this study (SARRP) represents a great advantage over the whole‐bone irradiator by limiting the radiation field with mm‐scale accuracy. Our past experiments have demonstrated that SARRP radiation on one bone has no adverse effects on the contralateral bones . In the current study, we performed bilateral tibial fractures, and the contralateral nonirradiated tibias healed at a similar pace as tibias from mice that have never received SARRP radiation (data not shown).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The focal irradiator used in this study (SARRP) represents a great advantage over the whole‐bone irradiator by limiting the radiation field with mm‐scale accuracy. Our past experiments have demonstrated that SARRP radiation on one bone has no adverse effects on the contralateral bones . In the current study, we performed bilateral tibial fractures, and the contralateral nonirradiated tibias healed at a similar pace as tibias from mice that have never received SARRP radiation (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…This clinical relationship between radiation therapy, fracture, and healing provided the impetus for utilizing radiation as a model to induce and study atrophy during bone regeneration. Previously, we used a focal irradiator (Small Animal Radiation Research Platform [SARRP]), which can mimic clinical focal radiation therapy in rodents with submillimeter accuracy, to delineate the mechanism of radiation damage on metaphyseal trabecular bone and to investigate potential treatments for this devastating condition . Here, we extended our research to traumatic bone fracture and established a highly reproducible and clinically relevant mouse nonunion model.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative analysis of the femur morphology and microarchitecture was performed using a micro–computed tomography (μCT) system (Micro‐CT 35; Scanco Medical AG, Brüttisellen, Switzerland) as described by de Bakker and colleagues and Chandra and colleagues . Femurs from 12‐week‐old Osx Cre/+ ; Rgs12 +/+ , Rgs12 fl/fl and Osx Cre/+ ; Rgs12 fl/fl mice of either gender ( n = 3 per gender, n = 6 in total of each group) were fixed with 4% (wt/vol) paraformaldehyde (PFA) for 24 hours, rinsed with PBS, and scanned.…”
Section: Methodsmentioning
confidence: 99%
“…Using baseline body mass to minimize intragroup differences, 8‐week‐old male Ts(17 16 )65Dn (Ts65Dn) mice and wild‐type (WT) mice (Jackson Laboratory, Bar Harbor, ME, USA) were randomly assigned to treatment (SclAb) or control vehicle‐treated (Vehicle) ( n = 4–6/group each) for a total of four groups with all animals assigned and housed individually by genotype: group 1, WT (placebo); group 2, WT‐SclAb; group 3, Ts65 (placebo); group 4, Ts65‐SclAb. The groups received either vehicle (isotonic vehicle buffer) or SclAb (100 mg/kg/wk, both kindly provided by Dr Michaela Kniessel, Novartis, Basel, Switzerland) as weekly iv injections in the morning on days 0, 7, 14, and 21 as previously described before euthanization on day 28. Measurements of body weight occurred at the same time per week to allow calculation of SclAb dose.…”
Section: Methodsmentioning
confidence: 99%